Sustainability is the new advantage : leadership, change, and the future of business - McAteer, Peter (Anthem Press, 2019)
'Sustainability Is the New Advantage' is a practical blueprint for leaders who want to start, develop, and grow sustainable organizations. The book provides stories and practical examples of how to assess challenges, create demonstrations projects, and scale the capabilities needed for sustainable business transformation